„All New Beginnings are Difficult?”—On Childhood, Politics and Philosophy - Weber, Barbara (ETHICS IN PROGRESS, 2011)
?Philosophizing with children? is not an entirely new concept: for example Plato already initiates his philosophical dialogues with young people. And even Kant in his essay What is Orientation in Thinking? (Kant 1991) calls for the early encouragement of reason.